2016
DOI: 10.1002/oti.1428
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Use of a Sensory Room in a Forensic Mental Health Setting: Staff and Patient Perspectives

Abstract: Despite the increased use of sensory rooms, there is little published evidence related to their benefits. The purpose of this study was to explore staff and patient perspectives of the use of a sensory room in an Australian forensic mental health setting. Staff and patients on a forensic hospital unit were recruited for this study. Focus group data was obtained from the perspective of the healthcare staff. A sensory assessment identified patients' sensory preferences. The details of the patients sensory room u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(81 citation statements)
references
References 16 publications
0
79
1
1
Order By: Relevance
“…; Smith & Jones ; Sutton et al . ; Wiglesworth & Farnworth ). Similarly, our findings align with research on how staff members perceive the effects of sensory rooms on patients’ well‐being and de‐escalation (Björkdahl et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Smith & Jones ; Sutton et al . ; Wiglesworth & Farnworth ). Similarly, our findings align with research on how staff members perceive the effects of sensory rooms on patients’ well‐being and de‐escalation (Björkdahl et al .…”
Section: Discussionmentioning
confidence: 99%
“…Wiglesworth and Farnworth () used a mixed methods design to explore the use of a sensory room on a forensic female inpatient ward from the perspectives of patients and staff. Similar to previous literature, the results showed that patients generally reported less distress after use of the room.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 6‐week programme consisting of both individual and group interventions of 1‐hour duration each was implemented in psychiatric intensive care settings and resulted in self‐reported reductions in arousal patterns after using the room (Gardner ). Wiglesworth and Farnworth () report that female service users in forensic settings engaging with the sensory room had significant reductions in stress.…”
Section: Introductionmentioning
confidence: 97%
“…Since then, Björkdahl et al . () and Wiglesworth and Farnworth () have also produced papers exploring staff and patient perspectives in more depth. This evaluation focuses on staff perspectives and experience of sensory interventions.…”
Section: Introductionmentioning
confidence: 99%